ANALISIS KINERJA JALAN MOHAMMAD TOHA DENGAN ATAU TANPA MARKA JALAN - Dedi Rusmayadi; An An Anisarida (Faculty of Engineering, Planning and Architecture, Winaya Mukti University, 2021)
Roads are infrastructure that is needed in the transportation system to connect one place to another in order to meet economic, social and cultural needs. Good road conditions are needed for smooth transportation activities, namely to accelerate the smooth mobilization of goods and services in a safe and comfortable manner. The high growth in the number of vehicles has an impact on traffic problems on the highway, such as what happened to Jalan Mohammad Toha. The purpose of this study is to determine how much the road capacity, the value of the degree of saturation, vehicle speed, travel time and road service level. The result of this research is that Jalan Mohammad Toha is an office area with several shops on the side of the road with a length of 0.2 km, a lane width of 12 m and a sidewalk width of 1.5m. and after conducting research on Jalan Mohammad Toha, it can be concluded that this road is included at service level C.